The Effect Of E-Wom And Accessibility On Destination Image And Its Impact On The Decision To Visit Bukittinggi Tourism Destinations By Domestic Travelers - asnimar; Yofina Mulyati (Institute of Computer Science (IOCS), 2022)
The study aims to find out the effect of Electronic Word of Mouth (E-WOM) and accessibility on destination image and their impact on domestic traveler visiting decisions in Bukittinggi City Tourism Destination. The type of study was quantitative research. The population comprised all domestic travelers to Bukittinggi city tourism destination in 2017, whose exact number was unknown, then around 246 persons were selected as a research sample. The sampling technique used was a nonprobability method with an accidental sampling approach. Method of Structural Equation Modeling - Partial Least Square data analysis (SEM-PLS) was employed to analyze data. The obtained results found that the direct influence of electronic word of mouth and accessibility has a positive and significant effect on the destination image. Electronic word of mouth has no significant impact on the visiting decision, and accessibility has a positive and significant effect on the visiting decision. The destination image has a positive and significant effect on the visiting decision. Meanwhile, the indirect effect of electronic word of mouth and accessibility has a positive and significant effect on the visiting decision through the destination image.